Identification and Incidence of Rice Diseases (Oryza sativa L.) in Conventional Land in Penebel Village - Rahayu, Diajeng Putri Ayu; Julyasih, Ketut Srie Marhaeni; Yuliastuti, Yuliastuti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Rice is a popular and widely consumed food crop in Indonesia, making disease a crucial factor in rice production. Penebel Village is a major rice producer, so disease damage significantly impacts rice productivity. This study was conducted to determine the types, characteristics, and incidence of rice plant diseases in conventional fields. The method used was exploratory descriptive, consisting of field surveys and interviews, as well as microscopic observations. Samples were taken using the quadrant method with five sampling points. Each point consisted of 16 plants, resulting in a total of 80 samples. Identification was performed using macromorphology. The rice plants observed were in the vegetative phase. The results of the study showed that in the rice fields were found Pyricularia sp. causing blast disease, Fusarium sp. causing fusarium wilt, Cercospora sp. causing narrow brown leaf spots, Helminthosporium sp. causing brown spots and Xanthomonas sp. causing bacterial leaf blight. The results of the calculation of disease incidence in conventional rice fields were blast (10%), fusarium (26.25%), leaf spots (16.25%), brown spots (51.25%), and bacterial leaf blight (50%). The results of the study indicate that the types, characteristics and incidence of diseases that appear in conventional agricultural land in Penebel village are very complex, so that more appropriate disease control is needed.